Transformation of catechol coupled to redox alteration of humic acids and the effects of Cu and Fe cations - Jia, Xiong; He, Yujie; Corvini, Philippe F.-X.; Ji, Rong (The Science of the total environment, 2020)
Humic substances are reactive during redox alteration. However, the role of this reactivity in the transformation of organic compounds and in carbon cycling in the environment is still unclear. Here, we used 14C-radioactive tracer to study abiotic transformation and humification of catechol, a representative of naturally occurring monomeric phenols and phenolic pollutants, in suspensions of humic acids (HAs) at original and H2/Pd-reduced redox states with flux of air (HAorg-Air and HAred-Air, respectively) or N2 (HAorg-N2 and HAred-N2, respectively) for 20 min in absence and presence of Cu(II) and Fe(II). Both HAorg and HAred can transform catechol in the absence of O2 to 19% and 25% of the initially applied amount, respectively. The transformation of catechol strongly increased when air was introduced, amounting to 75% in HAred-Air treatment and 43% in HAorg-Air treatment, owing to the generation of reactive oxygen species. Considerable amounts of catecholic carbons were incorporated into HAs (26% for HAred-Air and 19% for HAorg-Air), constituting humification of catechol. The presence of Cu(II) strongly inhibited the overall transformation and humification of catechol, although it significantly increased humification at the start of incubation. The presence of Fe(II) overall enhanced both the transformation and humification. The results provide first insights into the impacts of redox alteration of humic substances together with the presence of metal ions with variable valences on the fate of phenolic compounds in the environment. This study points out that redox alteration-induced abiotic transformation may be one important process for dissipation of phenolic pollutants and humification of phenolic carbons in environments rich in HAs and subject to redox fluctuation. [Display omitted] •Redox alteration of HAs is one abiotic process for environmental dissipation of phenolic compounds.•Oxidation of reduced HAs by O2 strongly stimulated catechol transformation.•Catecholic carbon was incorporated into HAs (i.e., humification) during oxidation.•Cu(II) markedly inhibited HAs-induced catechol transformation and humification.•Fe(II) overall increased catechol transformation and humification.